Expression study of Wnt/β-catenin signaling pathway associated lncRNAs in schizophrenia - Fatemeh Manafzadeh; Behzad Baradaran; Seyed Gholamreza Noor Azar; Kamran Javidi Aghdam; Reza Dabbaghipour; Asghar Shayannia; Soudeh Ghafouri-Fard (Annals of General Psychiatry)
Abstract Schizophrenia is one of the most debilitating mental illnesses affecting any age group. The mechanism and etiology of schizophrenia are extremely complex and multiple signaling pathways recruit genes implicated in the etiology of this disease. While the role of Wnt/β-catenin signaling in this disorder has been verified, the impact of long noncoding RNAs (lncRNAs) associated with this pathway has not been studied in schizophrenia. The objective of this study was to examine the expression levels of Wnt/β-catenin-related lncRNAs, namely CCAT2, SNHG5, PTCSC3, and DANCR, as well as the CTNNB1 gene encoding beta-catenin protein in two groups of schizophrenia patients (drug-naïve and medicated) compared with healthy individuals. This study included 50 medicated patients in the remission phase of the disease, 25 drug-naive patients in the acute phase, and 50 control subjects. There was no significant difference in CTNNB1 gene expression in the medicated patients compared to controls (P value = 0.9754). However, the expression of this gene was significantly decreased in drug-naïve first-episode patients compared with controls (P value < 0.001). In contrast, expression of DANCR, PTCSC3, SNHG5, and CCAT2 genes was significantly higher in medicated (P values < 0.001, < 0.001, = 0.01, < 0.001, respectively) and drug-naive first-episode patients (P value < 0.001) compared to control subjects. ROC curve analysis revealed that DANCR, PTCSC3, SNHG5, and CCAT2 genes had diagnostic power with specificity and sensitivity of 80% and above in separation between study subgroups. In brief, our data demonstrated dysregulation of Wnt/β pathway related genes and lncRNAs in the peripheral blood of patients with schizophrenia and their potential as biomarkers for this disorder.